Anesthetic strategy during endovascular therapy: General anesthesia or conscious sedation? (GOLIATH – General or Local Anesthesia in Intra Arterial Therapy) A single-center randomized trial. Issue 9 (December 2016) - Simonsen, Claus Z; Sørensen, Leif H; Juul, Niels; Johnsen, Søren P; Yoo, Albert J; Andersen, Grethe; Rasmussen, Mads
Rationale: Endovascular therapy after acute ischemic stroke due to large vessel occlusion is now standard of care. There is equipoise as to what kind of anesthesia patients should receive during the procedure. Observational studies suggest that general anesthesia is associated with worse outcomes compared to conscious sedation. However, the findings may have been biased. Randomized clinical trials are needed to determine whether the choice of anesthesia may influence outcome. Aim and hypothesis: The objective of GOLIATH (General or Local Anestesia in Intra Arterial Therapy) is to examine whether the choice of anesthetic regime during endovascular therapy for acute ischemic stroke influence patient outcome. Our hypothesis is that that conscious sedation is associated with less infarct growth and better functional outcome. Methods: GOLIATH is an investigator-initiated, single-center, randomized study. Patients with acute ischemic stroke, scheduled for endovascular therapy, are randomized to receive either general anesthesia or conscious sedation. Study outcomes: The primary outcome measure is infarct growth after 48–72 h (determined by serial diffusion-weighted magnetic resonance imaging). Secondary outcomes include 90-day modified Rankin Scale score, time parameters, blood pressure variables, use of vasopressors, procedural and anesthetic complications, success of revascularization, radiation dose, and amount of contrast media. Discussion: Choice of anesthesia may influence outcome in acute ischemic stroke patients undergoing endovascular therapy. The results from this study may guide future decisions regarding the optimal anesthetic regime for endovascular therapy. In addition, this study may provide preliminary data for a multicenter randomized trial.